Challenges Facing Women Career Mobility in Public and Private Universities in Kenya - Kibaara, Janerose Mutegi (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2016)
The study aimed at investigating the challenges affecting women career mobility in educational management in private and public universities in Kenya. The main objectives of the study were; to establish the challenges hindering women from progressing in their careers in public and private universities in Kenya, to examine the interventions put in place by both public and private universities in Kenya to address the challenges facing women in their career progression in private and public universities in Kenya. The following were the main findings of the Study: Women faced insurmountable barriers as they navigated through their career path in universities in Kenya. These challenges faced by women contributed to low number of women in the realm of university management in public and private universities in Kenya. Some of the challenges included: Lack of mentors, family responsibilities, lack of social networks, lack of training and development opportunities, socialization of men and women and aspirations of women, and cultural values and attitudes that view women as inferior. The study therefore concluded that there was need to change societal attitudes and cultural situation that influenced female participation in management to make them more competitive. There was need to put into practice a criteria for recruitment and promotion of university managers and implement available policies to increase women participation in university management and reduce the challenges that they encounter in their career mobility in public and private universities in Kenya.